Adipose invariant NKT cells interact with CD1d‐expressing macrophages to regulate obesity‐related inflammation. Issue 4 (28th February 2022) - Satoh, Masashi; Iizuka, Misao; Majima, Masataka; Ohwa, Chizuru; Hattori, Akito; Van Kaer, Luc; Iwabuchi, Kazuya
Abstract: Obesity is accompanied by and accelerated with chronic inflammation in adipose tissue, especially visceral adipose tissue (VAT). This low‐level inflammation predisposes the host to the development of metabolic disease, most notably type 2 diabetes. We have focused on the capacity of glycolipid‐reactive, CD1d‐restricted natural killer T (NKT) cells to modulate obesity and its associated metabolic sequelae. We previously reported that CD1d knockout (KO) mice are partially protected against the development of obesity‐associated insulin resistance, and these findings were recapitulated in mice with an adipocyte‐specific CD1d deficiency, suggesting that NKT cell–adipocyte interactions play a critical role in exacerbating disease. However, many other CD1d‐expressing cells contribute to the in vivo responses of NKT cells to lipid antigens. In the present study, we examined the role of CD1d expression by macrophages (Mϕ) in the development of obesity‐associated metabolic inflammation using LysMcre‐cd1d1 f / f mice where the CD1d1 gene is disrupted in a Mϕ‐specific manner. Unexpectedly, these animals contained a higher frequency of T‐bet + CD4 + T cells in VAT with increased production of Th1 cytokines that aggravated VAT inflammation. Mϕ from mutant mice displayed increased production of IL‐12p40, suggesting M1 polarization. These findings indicate that interactions of CD1d on Mϕ with NKT cells play a beneficial role in obesity‐associated VAT inflammation and insulin resistance with a sharp contrast to an aggravating role of CD1d in another type of antigen‐presenting cell, dendritic cells. Abstract : Function of iNKT cells and macrophage interaction in obesity.